2019
DOI: 10.30651/aks.v3i2.1648
|View full text |Cite
|
Sign up to set email alerts
|

Pencegahan Bullying di Sekolah Melalui Program “Welcome Day”

Abstract: This community service activity is motivated by the condition of problems in the environment of Junior High School (SMP) of Global Insani Islamic School (GIIS); it has been found that one of the problems that is deemed necessary to watch out is in terms of interaction with fellow Junior High School students. Based on the observation of the school, in this case is the teacher, the intercommunications of Junior High School students are considered "braver". In the sense of sometimes "forgetting" the risks or dang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Dengan demikian siswa dan siswi menjadi lebih dekat dan ini dapat mencegah perilaku bullying. Selain itu dalam kegiatan program tersebut peserta juga diajak untuk berdiskusi bersama serta diajak untuk mengidentifikasi perilaku yang tidak baik seperti bullying (Sarasati et al, 2019).…”
Section: Pendahuluanunclassified
“…Dengan demikian siswa dan siswi menjadi lebih dekat dan ini dapat mencegah perilaku bullying. Selain itu dalam kegiatan program tersebut peserta juga diajak untuk berdiskusi bersama serta diajak untuk mengidentifikasi perilaku yang tidak baik seperti bullying (Sarasati et al, 2019).…”
Section: Pendahuluanunclassified
“…Apart from that, several researchers also offer harsh punishments for perpetrators of bullying (Siddiqui et al, 2023) (Sung et al, 2020) (Yamada & Setyowati, 2023) (Mayasari & Rambe, 2023). Several other studies also attempt to handle bullying cases by offering strengthening character education in schools (Indramaya, 2023) (Zaenul, 2022) (Wulandari & Ningsih, 2023). From this research, we have not found anything that specifically discusses a spiritual approach to dealing with cases of bullying at school.…”
Section: Introductionmentioning
confidence: 99%